Determination of gestational time and prediction of parturition in dogs and cats: an update. (27th September 2016) - Beccaglia, M.; Alonge, S.; Trovo', C.; Luvoni, G. C.
Contents: Accurate prediction of delivery date in canine and feline allows a better management of parturition, reducing the loss of neonates. This review evaluates the most common methods adopted to accurately predict the day of delivery: determination of ovulation and hormonal assays, first appearance of embryonic/foetal structures using ultrasound or radiography, echographic measurement of extra‐foetal and foetal structures, or evaluation of foetal flux and heart rate. Determination of ovulation and hormonal assays at the time of breeding and close to pregnancy term is widely used to predict parturition in dogs (Concannon et al. American Journal of Veterinary Research 44, 1983, 1819; Hayer et al. Journal of Reproduction and Fertility, Suppl. 47, 1993, 93; Hase et al. Journal of Veterinary Medical Science, 62, 2000, 243; Kutzler et al. Theriogenology, 60, 2003a, 1187). In cats, some studies have been carried out, but no hormonal parameters for accurate prediction of parturition have been described so far (Buff et al. Journal of Reproduction and Fertility, Suppl. 57, 2001, 187; De Haas van Dorsser et al. Biology of Reproduction, 74, 2006, 1090; DiGangi et al. Journal of the American Veterinary Medical Association, 237, 2010, 1267; Dehnhard et al. Theriogenology, 77, 2012, 1088). Many studies suggested that gestational timing can be obtained by observation using ultrasound or radiography of specific structures in relation to the time of appearance during gestation (Concannon and Rendano American Journal of Veterinary Research, 44, 1983, 1506; Rendano et al. Veterinary Radiology, 25, 1984, 132; Shille and Gontarek Journal of the American Veterinary Medical Association, 187, 1985, 1021; Davidson et al. Veterinary Radiology, 27, 1986, 109; England et al. Journal of Small Animal Practice, 31, 1990, 324; Yeager et al. American Journal of Veterinary Research, 53, 1992, 342; Zambelli et al. Theriogenology, 57, 2002a, 1981; Zambelli et al. Journal of Feline Medicine and Surgery, 4, 2002b, 95; Zambelli and Prati 2006; Lopate Theriogenology, 70, 2008, 397; Davidson and Baker Topics in Companion Animal Medicine, 24, 2009, 55). Ultrasonographic measurement of extra‐foetal and foetal structures is a common and accurate method for the prediction of parturition day during pregnancy, when specific formulae are used depending on the ultrasonographic parameter, the species and, in canines, the size of the bitch (Shille and Gontarek Journal of the American Veterinary Medical Association, 187, 1985, 1021; England et al. Journal of Small Animal Practice, 31, 1990, 324; Luvoni and Grioni Journal of Small Animal Practice, 41, 2000, 292; Luvoni and Beccaglia Reproduction in Domestic Animals, 41, 2006, 27; Lopate Theriogenology, 70, 2008, 397; Michel et al. Reproduction in Domestic Animals, 46, 2011, 926; Beccaglia and Luvoni Reproduction in Domestic Animals, 47, 194, 2012). Recent studies demonstrated that in dogs, the imminence of parturition could be predicted by evaluating foetal flux and foetal heart rate by ultrasound (Gil et al. Theriogenology, 82, 2014, 933; Giannico et al., Animal Reproduction Science, 154, 2015, 105). For an accurate prediction of parturition date, the combination of different methods is desirable.